A decision model and cost analysis of intra-operative cell salvage during hepatic resection. Issue 5 (May 2016) - Lemke, Madeline; Eeson, Gareth; Lin, Yulia; Tarshis, Jordan; Hallet, Julie; Coburn, Natalie; Law, Calvin; Karanicolas, Paul J.
Abstract: Background: Intraoperative cell salvage (ICS) can reduce allogeneic transfusions but with notable direct costs. This study assessed whether routine use of ICS is cost minimizing in hepatectomy and defines a subpopulation of patients where ICS is most cost minimizing based on patient transfusion risk. Methods: A decision model from a health systems perspective was developed to examine adoption and non-adoption of ICS use for hepatectomy. A prospectively maintained database of hepatectomy patients provided data to populate the model. Probabilistic sensitivity analysis was used to determine the probability of ICS being cost-minimizing at specified transfusion risks. One-way sensitivity analysis was used to identify factors most relevant to institutions considering adoption of ICS for hepatectomies. Results: In the base case analysis (transfusion risk of 28.8%) the probability that routine utilization of ICS is cost-minimizing is 64%. The probability that ICS is cost-minimizing exceeds 50% if the patient transfusion risk exceeds 25%. The model was most sensitive to patient transfusion risk, variation in costs of allogeneic blood, and number of appropriate cases the device could be used for. Conclusions: ICS is cost-minimizing for routine use in liver resection, particularly when used for patients with a risk of transfusion of 25% or greater.